Isolated negative T waves in the general population is a powerful predicting factor of cardiac mortality and coronary heart disease. (15th January 2016) - Rollin, Anne; Maury, Philippe; Kee, Frank; Montaye, Michèle; Haas, Bernadette; Yarnell, John; Arveiler, Dominique; Amouyel, Philippe; Evans, Alun; Ducimetière, Pierre; Ferrières, Jean; Ruidavets, Jean-Bernard
Abstract: Background: Isolated negative T waves (INTW) are considered a common and minor electrocardiographic (ECG) abnormality. However, few recent studies have associated the presence of INTW with an increased risk of all-causes and cardiovascular mortalities. The aim was to evaluate the predictive value of INTW for coronary heart disease (CHD) and all-cause mortality. Methods: Between 1991 and 1994, 12-lead ECGs were recorded in a sample of 10, 600 men (PRIME Study). Among them, 1284 (12.1%) were excluded because of major ECG abnormalities at entry according to Minnesota code, a history of CHD or likely ischemic chest pain on the Rose Questionnaire. INTW were found in 256 subjects (2.74%). The primary outcome was myocardial infarction and angina pectoris after a 10 year follow-up (9.6 ± 1.4). Secondary outcome was all causes of death. Results: After multivariate adjustment, INTW < 1 mm in anterior or inferior leads was associated with a higher risk of angina pectoris [HR 3.04 95% CI (1.13–8.22) and HR 3.67 95% CI (1.35–9.96) respectively] and INTW ≥ 1 mm in lateral or anterior leads were associated with a higher incidence of myocardial infarction [HR 2.75, 95% CI (1.29–5.88) and HR 3.20 95% CI (1.68–6.09) respectively]. The association of INTW ≥ 1 mm in leads V1 to V5 with mortality remained highly significant [HR 3.17 95% CI (1.77–5.65)] after multivariate adjustment. Conclusions: In middle-age men, INTW is associated with a 2 to 3-fold higher risk of death, myocardial infarction and angina pectoris.